Penyelesaian Hutang Piutang Melalui Gugatan di Pengadilan Negeri - Gunawan, Handi; Lubis, Muhammad Ridwan (Universitas Medan Area, 2024)
In everyday life, often occurring amid society is the issue of disputes or disputes regarding accounts payable either between individuals and individuals or between individuals and legal entities, which cannot be resolved between them, and the way to resolve it is through filing a lawsuit in the District Court which is an independent agency authorized to hear and decide disputes over accounts payable or default. The purpose of this research is to find out the legal regulations related to accounts payable in a simple lawsuit. The research methodology applied is normative or doctrinal research which only uses secondary data sources such as laws and regulations, court decisions, legal theories, and opinions of legal experts which are then analyzed using qualitative normative analysis which ultimately results in two things, namely: